Intimate partner violence during pregnancy among married women in Putalibajar municipality, Nepal - Sharma, Rakshya; Kaphle, Hari Prasad (Frontiers in Psychology, 2023)
Introduction- Intimate Partner Violence during pregnancy (IPVDP) is increasingly being recognized as a significant problem in the developing world due to its adverse health consequences on both pregnant women and children. The objective of the study is to measure the magnitude of intimate partner violence during pregnancy and the factors associated with IPVDP. Methods- Community-based cross-sectional study was conducted among 263 married women with an extended postpartum period between October 2019- March 2020 in Putalibajar municipality, Western Nepal. A face-to-face interview was conducted and data were collected using an interview schedule. A chi-square test and binary logistic regression analysis were performed to examine the association between IPVDP and independent variables. Results- Among 263 women interviewed, 30% experienced IPV during pregnancy, the most common type of violence was controlling behavior (20.2%) followed by emotional (18.6%), sexual (10.6%), economical (6.1%), and physical violence (5.3%). It was observed that IPV was more likely to occur among women whose husbands consumed alcohol (AOR=3.171; CI 95%: 1.588-9.167), women whose husbands consumed tobacco (AOR =3.815; CI 95%: 2.157–7.265), women who usually received family support during pregnancy (AOR =2.948; CI 95%: 1.115-7.793) and women who did not decide on marriage timing (AOR =2.777; CI 95%: 1.331-5.792). Conclusion- Three out of ten pregnant women experienced IPVDP. To prevent violence, ensuring women’s empowerment, formulating strict law as well as discouraging the element of a violent milieu is important.